PENGARUH IKLIM ORGANISASI, PENGEMBANGAN KARIER DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN DI ARTOTEL SANUR BALI (ASB) - Ni Kadek Budi Sri Pertiwi; I Nengah Sudja; Yenny Verawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Human Resources is one of the basic capital in the development process, so that the quality of human resources must always be improved and directed in order to achieve an expected goal. Employees are the main asset of the organization and have a strategic role in the organization, namely as thinkers, planners, and controllers of organizational activities within the company. This study aims to determine the organizational climate, career development, and organizational commitment affect employee performance at Artotel Sanur Bali (ASB). The population used in this research is Artotel Sanur Bali (ASB) with 35 respondents. The sampling technique used was the study population or census method and 35 respondents at Artotel Sanur Bali (ASB). The data analysis technique used is multiple linear regression analysis. The results of this study indicate that organizational climate has a positive and significant effect on employee performance at Artotel Sanur Bali (ASB). Career development has a positive and significant effect on employee performance at Artotel Sanur Bali (ASB). Organizational commitment has a positive and significant effect on employee performance at Artotel Sanur Bali (ASB).